Monitoring deep-sea benthic biodiversity using environmental DNA approaches to compare trawled and untrawled sites - Oosthuizen, Delene (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.